2019
DOI: 10.1155/2019/8161495
|View full text |Cite
|
Sign up to set email alerts
|

HIV Care Continuum among Postpartum Women Living with HIV in Atlanta

Abstract: Introduction. While increased healthcare engagement and antiretroviral therapy (ART) adherence occurs during pregnancy, women living with HIV (WLWH) are often lost to follow-up after delivery. We sought to evaluate postpartum retention in care and viral suppression and to identify associated factors among WLWH in a large public hospital in Atlanta, Georgia. Methods. Data from the time of entry into prenatal care until 24 months postpartum were collected by chart review from WLWH who delivered with ≥20 weeks ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
4
8
0
Order By: Relevance
“…Many studies focused on US sample of post-partum women have recorded similar results (Adhikari et al, 2019;Meade et al, 2018Meade et al, , 2019. Our finding further contributes to evidence that the 3 months post-partum mark is a critical time point in which a significant number of WLWH are likely to disengage from treatment (Buchberg et al, 2015;Meade et al, 2018Meade et al, , 2019. Engagement at this critical point has been related…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Many studies focused on US sample of post-partum women have recorded similar results (Adhikari et al, 2019;Meade et al, 2018Meade et al, , 2019. Our finding further contributes to evidence that the 3 months post-partum mark is a critical time point in which a significant number of WLWH are likely to disengage from treatment (Buchberg et al, 2015;Meade et al, 2018Meade et al, , 2019. Engagement at this critical point has been related…”
Section: Discussionsupporting
confidence: 81%
“…Also, for the PCE final model, we included PPE as an independent variable to examine for any relationship between engagement at 3 months and at 12 months. This decision was supported by literature findings that have noted such associations (Adhikari et al, 2019;Meade et al, 2018Meade et al, , 2019. The final model for PCE (Table 7) was significant at p < .001.…”
Section: Re Sultssupporting
confidence: 78%
See 1 more Smart Citation
“…In order to support further development of maternity care guidelines for WLWH, our future studies will aim to better describe severe maternal morbidity and postpartum maternal health outcomes among WLWH. Furthermore, recent studies from the United States have highlighted a concerning gap in postpartum retention to HIV care, which has never been well characterized among WLWH living in Canada 38,39 . Our future studies will aim to provide a comprehensive view of the factors associated with adverse maternal health outcomes, and postpartum care retention.…”
Section: Discussionmentioning
confidence: 99%
“…Because pregnant patients often have more frequent medical visits and receive more resources, patients experiencing pregnancy may be more likely to be retained in care than those who are not. 24,25 The phrase "congenital HIV" was also associated with retention in care. While others have found that patients with perinatally acquired HIV have had poor retention in care, these studies were predominantly performed among adolescents and often around the transition from pediatric to adult HIV care.…”
Section: Discussionmentioning
confidence: 99%